Of inventorship and patent ownership: Examining the intersection between artificial intelligence and patent law - SAW, Cheng Lim (Institutional Knowledge at Singapore Management University, 2023)
Artificial intelligence (“AI”) has garnered much attention in recent years, with capabilities spanning the operation of self-driving cars to the emulation of the great artistic masters of old. The field has now been ostensibly enlarged in light of the professed abilities of AI machines to autonomously generate patentable inventions. This article examines the present state of AI technology and the suitability of existing patent law frameworks in accommodating it. Looking ahead, the authors also offer two recommendations in a bid to anticipate and resolve the challenges that future developments in AI technology might pose to patent law. In particular, the case is made for fully autonomous machine inventors to be recognised as “inventors” by statute and for patent ownership of AI-generated inventions to be granted to the owners of these machine inventors by default.